A new approach to modelling banks' equity volatility: Adding time-to-maturity jumps - Oliver Juhler Grinderslev; Kristian Loft Kristiansen (Danmarks Nationalbank, 2017)
We add discrete jumps in the time-to-maturity of a firm's debt to the model of Engle and Siriwardane (2015), such that changes in equity volatility can be explained by the volatility of the firm's assets, its market leverage and investors' perception of the time-to-maturity of the firm's debt. For banks a shortening of the time-to-maturity can be interpreted as investor worries over whether the bank will experience funding or solvency problems. In line with this we find that calm periods generally coincide with a long perceived time-to-maturity and that crisis periods, where some banks experienced problems of different sorts, are characterized by a short perceived time-to-maturity. Changing perceptions of the time-to-maturity are broadly consistent with changes in the probability of default extracted for a structural Merton model, suggesting that the information in the perceived time-tomaturity clearly relates to the solvency of the firm, but that other factors, e.g. liquidity, also play a role. For financial researchers the model has several advantages as it allows one to disentangle which underlying factors affect changes in equity volatility as well as giving an indication of how the financial markets view the robustness of a bank when it comes to risks that affect both the solvency and liquidity situation of the bank. – – Vi tilføjer spring i løbetiden for firmaers gæld i modellen foreslået af Engle og Siriwardane (2015). Ændringer i aktievolatiliteten forklares derfor med volatiliteten i firmaets aktiver, firmaets gearing og investorernes syn på gældens løbetid. En kort løbetid kan for banker fortolkes som bekymring fra investorerne for refinansieringen af bankens gæld og/eller bankens solvens. Konsistent med denne fortolkning finder vi, at rolige perioder generelt er sammenfaldende med lange løbetider, hvorimod kriseperioder generelt er karakteriseret ved korte løbetider. Ændringer i løbetiden er til en vis grad sammenfaldende med ændringer i probability of default udledt fra en Merton model, hvilket tyder på, at informationen i løbetiden er relateret til firmaets solvens, men at også andre ting, fx likviditet, er vigtige komponenter. Modellen har adskillige fordele, idet den dekomponerer aktievolatiliteten i de underliggende faktorer, og samtidig giver en indikation af de finansielle markeders syn på bankens robusthed, hvad angår solvens og likviditet.
Keywords: C32; G01; G12; G21; G32; 330; Financial stability; Financial sector; Financial risks; Models